An Experimental Platform with Rotating Airflow Excitation and Stationary Blisk Vibration Measurement. Issue 1 (February 2021) - Ouyang, Luohui; Bi, Qingzhen; Shang, Hai; Zhu, Limin; Yu, Jianhua
Abstract: With the question that the vibration of the realistic blisk in the engine is hard to be predicted, researchers need an experimental test platform to study the realistic dynamic properties and monitor the vibration of the designed blisk. For keeping the relative motion between airflow and blisk in a real engine, and facilitating the measurement of the blisk vibration, a new experimental platform with rotating air excitation and stationary blisk vibration measurement is developed in this paper. Firstly, the schematic diagram of the test platform is shown and all the components are illustrated clearly, including the stationary airflow excitation system, the test rig, and the vibration measurement system. Then two typical experiments are conducted with the designed academic blisk. A stationary excitation and a transient acceleration excitation are employed to the stationary blisk. Through the time-frequency analysis of the vibration signal measured by the Laser Doppler Vibrometer, the source of each component of the vibration signal is obtained. The experiment results show that the stationary and transient vibration of the blisk can be measured and identified correctly.